PERLINDUNGAN TERHADAP ANAK KORBAN TINDAK PIDANA BERDASARKAN UNDANG-UNDANG NOMOR 11 TAHUN 2012 - Fitra Oktoriny (Normative Jurnal Ilmiah Hukum, 2017)
The Child Criminal Court should provide guidance, guidance, education through the verdict imposed. Aspects of child protection in child criminal justice in terms of psychology aims to avoid violence, neglect, persecution and so forth. Our perspective can not be separated from the Criminal Justice System of the Child. Through the criminal justice process that issues children in providing protection to children and taking into account the rights of children. Criminal Justice Process both children as perpetrators and children as victims, then terterhadap child issues put forward Human Rights (HAM).